ANALISIS PENENTU EKSPOR KOPI INDONESIA - Bismo Try Raharjo (Jurnal Ilmiah Mahasiswa FEB, 2012)
Coffee is  one of the primary  exports  commodity  of Indonesia. Where Indonesia  is the third largest coffee producer in the world after Brazil and Vietnam with supply around 6% of total world coffee production, and Indonesia is the fourth largest coffee exporter in the world with the 11% market share of the world.  This research is aimed to assess the factors that influence the volume of Indonesia coffee exports. Researcher used the panel data regresion as method of this research and secondary data of 1994-2010 as the type of research data with 8 importers countries as the object of the study The result of this research concluded that the factors significantly affect the volume of Indonesia coffee exports are real PDB of importer countries, exchange rate Rupiah to US Dollar, and retail price of the importer countries. However, the monetary crisis of the year 1998 affect to the volume of Indonesia coffee exports.Keywords : Coffee, Export, International trade